2017
DOI: 10.1007/s00424-017-2046-3
|View full text |Cite
|
Sign up to set email alerts
|

The naked mole-rat exhibits an unusual cardiac myofilament protein profile providing new insights into heart function of this naturally subterranean rodent

Abstract: The long-lived, hypoxic-tolerant naked mole-rat well-maintains cardiac function over its three-decade-long lifespan and exhibits many cardiac features atypical of similar-sized laboratory rodents. For example, they exhibit low heart rates and resting cardiac contractility, yet have a large cardiac reserve. These traits are considered ecophysiological adaptations to their dank subterranean atmosphere of low oxygen and high carbon dioxide levels and may also contribute to negligible declines in cardiac function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…Prior studies have reported H . glaber heart morphology and physiology [34, 35], although CM polyploidy had not been addressed. We conducted an analysis of ventricular CM composition in juvenile-adult stage naked mole-rats, using the same procedures as used for mouse heart analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have reported H . glaber heart morphology and physiology [34, 35], although CM polyploidy had not been addressed. We conducted an analysis of ventricular CM composition in juvenile-adult stage naked mole-rats, using the same procedures as used for mouse heart analysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, two of the proteins significantly altered between the mouse and bat skeletal muscle are best known for their distribution in cardiac muscle, namely myosin light chain 2 and fatty acid binding protein 3 (FABP3) [31,32]. Myosin light chain 2 has been found to have half the levels of phosphorylation in the naked mole rat when compared with the mouse, which makes this an especially interesting protein in exceptionally long-lived species [33]. We have now confirmed that FABP3 is much more abundant in the bat muscle mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…High resolution 1 H MRS based metabolomic analysis of NMR heart tissue (representative spectra shown in figure 1) revealed distinctly different metabolomic profiles compared to C57/BL6 hearts (figure 2 b ) and changes in several key metabolites were observed (figure 2 c , d ). Despite reduced contractile performance and baseline hypertrophy [1215], NMR hearts were not energetically compromised as the levels of creatine and ATP were comparable to C57/BL6 wild-type hearts. Myocardial glycogen and glucose-1-phosphate levels (G-1-P) resulting from glycogen turnover were significantly higher in the NMR hearts and were undetectable in C57/BL6 mouse hearts ( p < 0.001; figure 2 e ).…”
Section: Resultsmentioning
confidence: 99%